Artificial Intelligence and the Problem of Digital Ontotheology: Toward a Critical Rethinking of Science Fiction as Theory. (June 2015) - Crombez, Joel; Dahms, Harry F.
In utopian/science fiction literature, comprehensive knowledge is a familiar motif that also inspires recent policies to screen society through surveillance. In the late 20th century, a digital archive promised to facilitate quick access to abundant information and effective strategies to confront myriad challenges. Yet, today, the scale and scope of information accumulation in national and corporate repositories is reaching proportions whose intelligent processing excedes human capabilities, and triggering a shift in focus from dumb repository to artificial intelligence. Processing such accumulation of knowledge necessiates skills commonly attributed to divinity. Without a theory that recognizes this condition and informs the operations of artificial intelligence, the latter is likely to fail in human ways, e.g., by perceiving false patterns resulting from flawed theories assigning meaning to knowledge. For successful pattern recognition to occur, theories must rest on science fiction and a digital ontotheology of the machine as the form this archive assumes.